Assessing Plan B: The Effect of the Morning After Pill on Children and Women. (20th April 2017) - Bentancor, Andrea; Clarke, Damian
Abstract : We test whether the availability of the emergency contraceptive ('morning after') pill in the absence of legalised abortion can have effects similar to those of other large‐scale contraceptive reforms. To do so, we examine a quasi‐experimental policy reform occurring in Chile in 2008. Using vital statistics covering all births and foetal deaths over the period 2006–12, we show that the availability of the emergency contraceptive pill reduces pregnancy and early gestation foetal death, which we argue proxies for illegal abortion. Our results suggest that in the context of Chile, a country with among the most restrictive abortion laws in the world, the emergency contraceptive pill had effects around a third as large as various abortion reforms observed in other contexts.